Drug targets and biomarker identification from computational study of human notch signaling pathway - Chowdhury, Saikat; Sarkar, Ram Rup (Clinical and Experimental Pharmacology and Physiology, 2013)
Notch signaling pathway is widely implicated in controlling various cellular functions, cell fate determination, and stem cell renewal in human but aberrant activity in cancer stem cells may cause different types of cancers. Understanding the complexity of this pathway to identify important targets for cancer therapy and to suppress the pathway activity without affecting the normal functions is of utmost importance to clinical and experimental pharmacologists. For developing therapeutic strategy, non availability of detailed molecular interactions, complex regulations and cross talks with other pathways pose a serious challenge to get a coherent understanding of this pathway. This motivated us to reconstruct the largest human cell specific Notch pathway with more number of molecules and interactions available from literatures and databases. To identify probable drug targets and biomarkers for cancer prognosis, we also performed computational study of the pathway using structural and logical analysis and identified important hub proteins, cross talks and feedback mechanisms. The model simulation is validated using reported mRNA expression profile in Glioblastoma cell line and the predictions not only show significant accuracy but also able to identify the undetermined expressions. From our simulation, to identify novel combinations of drug targetable proteins and better substitute for GAMMA SECRETASE inhibition, we proposed two alternative scenarios: partial suppression of Notch target proteins by NICD1 & HIF1A; and complete suppression by NICD1 & MAML, in Glioblastoma cell line. This reconstructed Notch signaling pathway and the computational analysis for identifying new biomarkers and combinatory drug targets will be useful for future in-vitro and in-vivo analysis to control different cancers

Data in support of large scale comparative codon usage analysis in leishmania and trypanosomatids - Subramanian, Abhishek; Sarkar, Ram Rup (Data Brief, 2015)
This data article contains data related to the article “Comparison of codon usage bias across Leishmania and Trypanosomatids to understand mRNA secondary structure, relative protein abundance and pathway functions” by Subramanian and Sarkar [1]. The data comprises of sequence-based measures that quantify the effect of codon usage across genomes. The data thus generated represents computed values of codon usage indices like relative synonymous codon usage (RSCU), effective number of codons (ENC), and codon adaptation index (CAI), a set of single copy orthologous genes common to the 13 Trypanosomatids, and comparisons of CAI between genes of different functions. This forms a basis of comparison to infer the causes and consequences of codon usage bias in Leishmania and other Trypanosomatids.

Dissecting leishmania infantum energy metabolism - a systems perspective - Subramanian, Abhishek; Jhawar, Jitesh; Sarkar, Ram Rup (Plos One, 2015)
Leishmania infantum, causative agent of visceral leishmaniasis in humans, illustrates a complex lifecycle pertaining to two extreme environments, namely, the gut of the sandfly vector and human macrophages. Leishmania is capable of dynamically adapting and tactically switching between these critically hostile situations. The possible metabolic routes ventured by the parasite to achieve this exceptional adaptation to its varying environments are still poorly understood. In this study, we present an extensively reconstructed energy metabolism network of Leishmania infantum as an attempt to identify certain strategic metabolic routes preferred by the parasite to optimize its survival in such dynamic environments. The reconstructed network consists of 142 genes encoding for enzymes performing 237 reactions distributed across five distinct model compartments. We annotated the subcellular locations of different enzymes and their reactions on the basis of strong literature evidence and sequence-based detection of cellular localization signal within a protein sequence. To explore the diverse features of parasite metabolism the metabolic network was implemented and analyzed as a constraint-based model. Using a systems-based approach, we also put forth an extensive set of lethal reaction knockouts; some of which were validated using published data on Leishmania species. Performing a robustness analysis, the model was rigorously validated and tested for the secretion of overflow metabolites specific to Leishmania under varying extracellular oxygen uptake rate. Further, the fate of important non-essential amino acids in L. infantum metabolism was investigated. Stage-specific scenarios of L. infantum energy metabolism were incorporated in the model and key metabolic differences were outlined. Analysis of the model revealed the essentiality of glucose uptake, succinate fermentation, glutamate biosynthesis and an active TCA cycle as driving forces for parasite energy metabolism and its optimal growth. Finally, through our in silico knockout analysis, we could identify possible therapeutic targets that provide experimentally testable hypotheses.

Dynamics of gli regulation and a strategy to control cancerous situation: hedgehog signaling pathway revisited - Subramanian, Abhishek; Sarkar, Ram Rup (Journal of Biological Systems, 2015)
The hedgehog signaling cascade generates highly diverse, fine-tuned responses in response to the external stimulus by the sonic hedgehog (SHH) protein. This is required for the flawless functioning of the cell, its development, survival and proliferation; maintained through production of Glioma protein (GLI) and transcriptional activation of its target genes. Any change in the behavior of GLI response by ectopic expression of SHH or mutations in the core pathway components may cause serious consequences in the cell fate through rapid, uncontrolled and elevated production of GLI. Here, we present a simple but extensive computational model that considers the detailed reaction mechanisms involved in the hedgehog signal transduction and provides a detailed insight into regulation of GLI. For the first time, by explicit involvement of suppressor of fused (SUFU) and Hedgehog interacting protein (HHIP) reaction kinetics in the model, we try to demonstrate the vital importance of HHIP and SUFU in maintaining the graded response of GLI in response to SHH. By performing parameter variations, we capture the conversion of a graded response of GLI to an ultrasensitive switch under SUFU-deficient conditions that might predispose abnormal embryonic development and the irreversible switching response of GLI that corresponds to signal-independent pathway activation observed in cancers.
Keywords: GLI Dynamics; Graded Response; Hedgehog Signaling Pathway; Ligand-Dependent and -Independent Pathway Activation; Ultrasensitive and Irreversible Switch

Differential suitability of reactive oxygen species and the role of glutathione in regulating paradoxical behavior in gliomas: a mathematical perspective - Bhowmick, Rupa; Sarkar, Ram Rup (PloS One, 2020)
Manipulative strategies of ROS in cancer are often exhibited as changes in the redox and thiol ratio of the cells. Cellular responses to oxidative insults are generated in response to these changes which are triggered due to the rerouting of the metabolic framework to maintain survival under stress. However, mechanisms of these metabolic re-routing are not clearly understood and remained debatable. In the present work, we have designed a context-based dynamic metabolic model to establish that the coordinated functioning of glutathione peroxidase (GTHP), glutathione oxidoreductase (GTHO) and NADPH oxidase (NOX) is crucial in determining cancerous transformation, specifically in gliomas. Further, we propose that the puzzling duality of ROS (represented by changes inh(2)o(2)in the present model) in exhibiting varying cellular fates can be determined by considering simultaneous changes innadph/nadp(+)andgsh/gssgthat occur during the reprogramming of metabolic reactions. This will be helpful in determining the pro-apoptotic or anti-apoptotic fate of gliomas and can be useful in designing effective pro-oxidant and/or anti-oxidant therapeutic approaches against gliomas.

Differential cellular communication in tumor immune microenvironment during early and advanced stages of lung adenocarcinoma - Shukla, Mudita; Sarkar, Ram Rup (Molecular Genetics and Genomics, 2024)
Heterogeneous behavior of each cell type and their cross-talks in tumor immune microenvironment (TIME) refers to tumor immunological heterogeneity that emerges during tumor progression and represents formidable challenges for effective anti-tumor immune response and promotes drug resistance. To comprehensively elucidate the heterogeneous behavior of individual cell types and their interactions across different stages of tumor development at system level, a computational framework was devised that integrates cell specific data from single-cell RNASeq into networks illustrating interactions among signaling and metabolic response genes within and between cells in TIME. This study identified stage specific novel markers which remodel the cross-talks, thereby facilitating immune stimulation. Particularly, multicellular knockout of metabolic gene APOE (Apolipoprotein E in mast cell, myeloid cell and fibroblast) combined with signaling gene CAV1 (Caveolin1 in endothelial and epithelial cells) resulted in the activation of T-cell mediated signaling pathways. Additionally, this knockout also initiated intervention of cytotoxic gene regulations during tumor immune cell interactions at the early stage of Lung Adenocarcinoma (LUAD). Furthermore, a unique interaction motif from multiple cells emerged significant in regulating the overall immune response at the advanced stage of LUAD. Most significantly, FCER1G (Fc Fragment of IgE Receptor Ig) was identified as the common regulator in activating the anti-tumor immune response at both stages. Predicted markers exhibited significant association with patient overall survival in patient specific dataset. This study uncovers the significance of signaling and metabolic interplay within TIME and discovers important targets to enhance anti-tumor immune response at each stage of tumor development.
Keywords: Early and advanced stages of Lung Adenocarcinoma; Immunomodulation; Multicellular communication; Signaling-metabolic cross-talks; Tumor immune microenvironment; Tumor immunological heterogeneity

Dynamic cellular responses to gravitational forces: exploring the impact on white blood cell(s) - Murali, Anirudh; Sarkar, Ram Rup (Biomicrofluidics, 2024)
In recent years, the allure of space exploration and human spaceflight has surged, yet the effects of microgravity on the human body remain a significant concern. Immune and red blood cells rely on hematic or lymphatic streams as their primary means of transportation, posing notable challenges under microgravity conditions. This study sheds light on the intricate dynamics of cell behavior when suspended in bio-fluid under varying gravitational forces. Utilizing the dissipative particle dynamics approach, blood and white blood cells were modeled, with gravity applied as an external force along the vertical axis, ranging from 0 to 2 g in parameter sweeps. The results revealed discernible alterations in the cell shape and spatial alignment in response to gravity, quantified through metrics such as elongation and deformation indices, pitch angle, and normalized center of mass. Statistical analysis using the Mann-Whitney U test underscored clear distinctions between microgravity (<1 g) and hypergravity (>1 g) samples compared to normal gravity (1 g). Furthermore, the examination of forces exerted on the solid, including drag, shear stress, and solid forces, unveiled a reduction in the magnitude as the gravitational force increased. Additional analysis through dimensionless numbers unveiled the dominance of capillary and gravitational forces, which impacted cell velocity, leading to closer proximity to the wall and heightened viscous interaction with surrounding fluid particles. These interactions prompted shape alterations and reduced white blood cell area while increasing red blood cells. This study represents an effort in comprehending the effects of gravity on blood cells, offering insights into the intricate interplay between cellular dynamics and gravitational forces.